Knowledge, attitude and behavior towards COVID-19 among the Turkish healthcare workers - Yasin Uzuntarla; Sumeyra Ceyhan (National Scientific Medical Center, 2020)
Aim: Coronavirus disease 2019 (COVID-19) cases and the number of deaths linked to this disease have been increasing day by day, turning into a global health problem. Healthcare workers play a key role in the fight against COVID-19. It is aimed to determine the level of knowledge, attitude and behavior of Turkish healthcare workers towards COVID-19. Material and methods: This cross-sectional study was carried out with healthcare workers working in two state hospitals in Ankara and Bingol, Turkey. The participation rate in the survey was 76%, and the survey was completed by 836 healthcare workers. Results: 56.3% of the participants are women, 64.9% are married and 44.9% are nurses. It was found that 85% of the healthcare workers had a medium level of knowledge, 87% had a high level of attitude and 89% had a high level of behavior. In addition, a significant difference was found in the knowledge level of healthcare workers according to monthly income level and profession, and their behaviors by age (p<0.05). Conclusion: There is a significant positive correlation between knowledge, attitude and behavior towards COVID-19. Healthcare workers' training curricula and in-service training should provide information that will improve their knowledge, attitudes and behaviour towards COVID-19.